Murders and violations of human rights of transvestites and transgenders in Brazil: An approach based on the antra dossier and reflections on bolsonarism and police violence - Silva , Cleusa Gomes da; Grigoleto , Juliane Mayer; Kurschner , Rafael de Lima (Seven Editora, 2023)
This article seeks to reflect on Bolsonarism and police violence with a focus on the murder and violation of the human rights of transvestites and transgenders in Brazil. Our research problem is to analyze the influence of bolsonarism on police violence when it comes to the murder of trans and transvestite people. The methodology used is the bibliographic and documentary analysis of the ANTRA dossier on the murder of transgenders and transvestites. DOI:https://doi.org/10.56238/alookdevelopv1-058